Advanced PIC-MCC simulation for the investigation of step-ionization effect in intermediate-pressure capacitively coupled plasmas. (19th February 2018) - Kim, Jin Seok; Hur, Min Young; Kim, Chang Ho; Kim, Ho Jun; Lee, Hae June
Abstract: A two-dimensional parallelized particle-in-cell simulation has been developed to simulate a capacitively coupled plasma reactor. The parallelization using graphics processing units is applied to resolve the heavy computational load. It is found that the step-ionization plays an important role in the intermediate gas pressure of a few Torr. Without the step-ionization, the average electron density decreases while the effective electron temperature increases with the increase of gas pressure at a fixed power. With the step-ionization, however, the average electron density increases while the effective electron temperature decreases with the increase of gas pressure. The cases with the step-ionization agree well with the tendency of experimental measurement. The electron energy distribution functions show that the population of electrons having intermediate energy from 4.2 to 12 eV is relaxed by the step-ionization. Also, it was observed that the power consumption by the electrons is increasing with the increase of gas pressure by the step-ionization process, while the power consumption by the ions decreases with the increase of gas pressure.